Analisa investasi dengan Feasibility Study untuk meningkatkan Kecerdasan Finansial pada Budi Daya Ikan di Sidoarjo - Khumairoh, Nur Sitti (Program Doktor Ilmu Ekonomi, 2013)
Potential of each region in Indonesia from region to region and different. Indonesia has many islands and is surrounded by sea certainly has the potential of natural resources are not unlimited. One of the areas in Indonesia that fish is also a producer of Sidoarjo regency. Sidoarjo regency in East Java is located between two major rivers namely River Porong and Surabaya River so famous as the city of Delta. Which of the three investment potential of the aquaculture of milkfish, shrimp and Tilapia vaname who earn higher incomes?, Does investment analysis with feasibility studies to improve financial intelligence on aquaculture farmers. Whether or not a project implemented successfully in this case could provide economic benefits or provide financial benefits to the company the necessary analysis or assessment of the situation and the prospects of a project taking into account several criteria such as objectives, benefits and aspects related to the project in research project feasibility analysis. To find out more about the three types of resources are then conducted a field study. From the data collected by the theory of feasible study capital budgeting and financial analysis, data is processed to find out from the three farms that produce high profits. While the capital budgeting analysis that is used is the net present value (NPV), internal rate of return (IRR), payback period (PP), average rate of return (ARR) and Profitability Index (PI). From the calculation results can be seen that when viewed from the side of the capital vaname shrimp cultivation requires a smaller capital. in terms of earnings before interest and tax of tilapia aquaculture generate greater revenues. Pay back period of milkfish cultivation period of more rapid return of investment when compared with the cultivation of other woods. Internal rate of return calculations show that the cultivation of fish internal rate of returnnya higher than other cultivation. If you look at the results of the study fish ponds can be used as an investment option, because the investments are in need of smaller and faster payback periodnya. Another thing that underlies this selection of fish culture management easier and more powerful survival compared with other cultivation.Â Keywords: Investment Analysis, Fisheries, financial intelligence.